THE IMPACT OF FINTECH, ONLINE MARKETING, AND FINANCIAL INCLUSION ON THE DEVELOPMENT OF MSME ENTERPRISES IN KUNINGAN REGENCY, WEST JAVA - Suhardi, Dadang; Gunawan, Wely Hadi; Watulandi, Micki (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
This study aims to analyze the impact of financial technology (fintech), digital marketing, and financial inclusion on the growth of Micro, Small, and Medium Enterprises (MSMEs). In today's digital era, MSMEs face challenges in remaining competitive and relevant. This study seeks to understand how the use of fintech can provide easier access to financing sources and financial services, how digital marketing can enhance visibility and market penetration, and how financial inclusion can open opportunities for MSMEs that have been underserved by traditional banking services. The research methodology involves collecting data through surveys and interviews with MSME owners, as well as quantitative the data. The results show that the adoption of fintech and digital marketing has a significant positive impact on MSME business growth. Furthermore, financial inclusion plays a crucial role in supporting MSMEs' access to the financial services they need. The study concludes that a combination of fintech, digital marketing, and financial inclusion can be key factors in driving the growth and sustainability of MSME businesses. Therefore, the government and stakeholders are encouraged to provide the necessary support to enhance technology adoption and access to financial services for MSMEs.